IoT Based Automated and Remote Monitored Greenhouse Irrigation System for the Zimbabwe Open University Farm - Chimana, Ezekiel; Gombiro, Cross; Nyambo, Benny; Dzinavatonga, Kaitano; Mabuyaye, Charity; Mutero, Trust; Nemerai, Trust; Mlambo, Edmore; Rupere, Taurayi; Mhlanga, Plaxedes; Jowa, Viola (Indian Journal of Computer Science, 2024)
The present paper presents the design and development of an IoT-based automatic greenhouse farm mechanization and remote monitoring prototype system aimed at enhancing agricultural practices and promoting sustainable agriculture. The study focuses on the case of Zimbabwe Open University Farm in Manicaland province in Zimbabwe, highlighting the challenges faced in traditional farming methods and proposing an innovative solution based on IoT technologies. The objective was to develop a robust architecture and framework that integrates smart sensors and data analytics to automate various farming processes, optimize resource utilization, and enable remote monitoring and controlling irrigation and IoT enabled devices. The researchers propose a prototype system to help farmers increase agricultural yields with less manual labour. The system uses soil moisture sensor, heater, and fan and light bulb sensor to measure the soil moisture, switch on fan, heater, and light sensors. The obtained sensor values were viewed by the users through the Wi-Fi router and the decision is made through the mobile application whether to irrigate or not. The system is also intelligent enough to automatically carry out the irrigation when the soil moisture is low. The researchers used an IoT architecture model, microcontrollers, a proposed system architecture, and Android based application to develop an IoT remote monitored irrigation system for a greenhouse system. The results of prototype testing andÂ observations showed that the system was able to irrigate and monitor the greenhouse environment by using IoT smart technologies.